(untitled) (Journal of Environmental Science and Natural Resources, 2022)
Amla is sour and astringent taste fruit, making the fruit less palatable to eat directly as fresh fruit; hence it can be consumed in processed form. Preparing powder and candy from amla fruit can increase its acceptability, the market value of it and be utilized to develop new value-added products. Considering this, the present study was designed to evaluate the nutritional compositions, vitamin C content, beta-carotene content, and antioxidant activity of fresh amla and two amla products such as amla powder and amla candy. Between the two products, amla powder contained a significantly (P < 0.05) high amount of dietary fiber (17.67%), protein (4.98%), and ash (9.82%) contents than fresh amla and amla candy. Between two products, vitamin C (298.3 mg/100gm) and beta-carotene (113.55 mg/100gm) contents were significantly (P < 0.05) high in amla powder. But amla candy showed high antioxidant activity (77.75%) than amla powder (59.2%). Results of this study suggested that amla and amla products are a good source of nutrients like vitamin C and different bioactive components. Amla can be utilized in diets as candy and dehydrated powder or flour which is easily included in food formulations due to its excellent nutritional qualities. Optimization of its use is beneficial in terms of nutritional and economical points of view. Environ. Sci. & Natural Resources, 13(1&2): 82-86, 2020